Meditation and Hypnosis: Two Sides of the Same Coin?. Issue 2 (3rd April 2017) - Facco, Enrico
Abstract: Hypnosis and meditation, as a whole, form a heterogeneous complex of psychosomatic techniques able to control mind and body regulation. Hypnosis has been pragmatically used for limited therapeutic targets, while Eastern meditation has much wider philosophical and existential implications, aiming for a radical liberation from all illusions, attachments, suffering and pain. The available data on the history, phenomenology, and neuropsychology of hypnosis and meditation show several common features, such as the following: (a) induction based on focused attention; (b) capability to reach an intentional control of both biologic-somatic activities and conscious-unconscious processes; (c) activation/deactivation of several brain areas and circuits (e.g., the default modality network and pain neuromatrix) with a relevant overlapping between the two.